(untitled) (New York, 1959)
This volume of essays is sponsored by the Inter-University Study of Labor Problems in Economic Development. Most of the chapters are based upon research financed by this study. Each essay is eventually to be the subject of a separate monograph. The financial support of the study by the Ford Foundation is gratefully acknowledged.
Keywords: Labor and laboring classes,Lao động và các lớp lao động; History,Lịch sử